Capital market intermediation and manufacturing sector financing in Nigeria - Rosemary, Ikeobi Nneka (International Journal of Business Management and Finance Research, 2023)
This paper assesses the intermediary role of the Nigerian Capital Market in financing the manufacturing sector, by examining the relationships between proxies of capital market intermediation and manufacturing output. To examine the relationships, secondary data covering a 13-year period from 2008 to 2020 were obtained from the Statistical Bulletin of the Central Bank of Nigeria. The secondary data included manufacturing output (MANUF), market capitalization (MCAP), equities (EQUITY) and corporate bonds (CORPBD). Manufacturing output was used as dependent variable, while capital market instruments, namely, equities and corporate bonds were proxies for capital market intermediation. Market capitalization was also included as proxy for capital market intermediation. Analysis was carried out using a multiple regression model and ordinary least squares technique. Results showed that market capitalization has positive and significant impact on manufacturing output; corporate bonds have negative but insignificant impact while equities have significant negative impact on manufacturing output. These findings have shown that although the Nigerian capital market possesses the potential to mobilize funds from the economy, it was not a source of finance for the manufacturing sector. It is therefore recommended that effort should be made by policy makers to remove all identified impediments that would deter entrepreneurs and manufacturing firms from accessing funds from the capital market.